Placental and liver nutritional factors in the pathogenesis of preeclampsia - Castelazo Ayala, Luis (2015)
The authors have studied 92 cases of toxemia since a nutritional point of view. In 162 more potients they have studied the morphology of placenta. A third group of patients was formed by 54 cases of toxemia complicated with diabetes; 94 patients with toxemia and mola; 234 of multiple pregnancy and toxemia and 15 cases of fetal hydropesia in toxemic patients; histological studies of placental tissue were performed in most of the cases; as control they have 55 placentas from normal deliveries. After a discussion of pertinent data, the authors assume that the damage of the liver in patients with toxemia of pregnancy is secundary to the disease, and that the some relation occurs between the infarcts of placenta and the disease. lt is postulated that patients with diabetes mellitus and mola hydatiform as those with fetal hydropesia suffer a kind of toxemia different of the "pure type".